Investors’ Behavior Placing Orders in Indonesia Stock Exchange - Syamni, Ghazali (The Indonesian Capital Market Review, 2011)
The objective of this research is to analyze the behavior pattern of trading volume at opening and closing of market in Indonesia Stock Exchange. The behaviors pattern is structured by investors' decision in placing buy and sell orders. This research used intraday data transaction history-corporate edition demand and order history stock which included in pre-opening and LQ-45 in Indonesia Stock Exchange on March, April, and Mei 2005. The result of this research is investor place bigger order on the opening and closing markets than period trading. This shows that they are more carefully and more conservative in doing trades on the opening session. This can occur because of the large orders at the market opening is not necessarily for investors to execute the transaction order status match. Research has found that the pattern of investors in making orders morning session has a reverse J pattern and a pattern of J at afternoon session. Reverse J pattern in the morning session subject to lunch time and most of these patterns of behavior are driven by more dominant sell orders in comparison to buy orders, while the afternoon session or the closing of the market is caused by of investors who want to realize higher transaction match. Other implication is investors must be more active in observing all of the information in doing trading on pre opening, during, and closing of market.